National and international policies to control illegal forest activities: a report prepared for the Ministry of Foreign Affairs, Government of Japan - Tacconi, L.; Boscolo, M.; Brack, D. (Center for International Forestry Research, 2003)
Illegal forest activities pose a significant threat to the sustainability of forest ecosystems, result in losses of government revenues, foster a vicious cycle of bad governance, and may contribute to increased poverty and social conflict. As such, they have received considerable attention from the international community, particularly in recent years. The purpose of this study is to critically examine the range of national and international policy options available to reduce illegal forest activities by: (i) reviewing what is known regarding the nature and extent of the problem, (ii) identifying possible policy responses applicable by producer countries, by consumer countries, or via international initiatives, and (iii) suggesting possible principles and criteria for further evaluation and selection of policy options. The report concludes by outlining principles and criteria to aid the development of appropriate policy options to reduce illegal forest activities.